Prenosni sistem za merjenje temperaturnih profilov v industrijskih pečeh - Glogovac, Branislav (Materiali in tehnologije, 2001)
Industrial furnaces are mostly controled by a measurement of the "furnace temperature" using a roof- or wall-mounted thermocouple. This classical control method is often unsatisfactory and with discontinuous furnace operations can lead to wide variations in the disscharge stock temperature. The actual steel temperatures were measured with trailing thermocouples. The complete portable system for measurement of temperature profiles in industrial furnace has been calibrated in the laboratory.
Keywords: merjenje temperature; termoelementi; temperaturni profil; industrijske peči